Technology Mediation Programs and SME Innovative Activities - Gunasekara, Chrys (Prabandhan: Indian Journal of Management, 2011)
Government-sponsored technology mediation programs for SMEs are widely regarded as important elements in the constitution of innovation systems. These programs partially overcome the barriers that face SMEs in gaining access to new technologies, related to cost, resources and absorptive capacity. This study examines the impacts of a government-sponsored technology access program in Australia for SMEs in manufacturing, in the context of the sources of innovation more generally. The study finds that, while the program itself was seen as beneficial, the scope and value of benefits were unclear, as was the linkage between the program outputs and the broader innovative activities of the firms. Implications for program design are suggested.